2021
DOI: 10.4269/ajtmh.21-0087
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene Practices and Challenges during the COVID-19 Pandemic: A Cross-Sectional Study in Rural Odisha, India

Abstract: Abstract.Water, sanitation, and hygiene (WASH) practices emerged as a critical component to controlling and preventing the spread of the COVID-19 pandemic. We conducted 131 semistructured phone interviews with households in rural Odisha, India, to understand behavior changes made in WASH practices as a result of the pandemic and challenges that would prevent best practices. Interviews were conducted from May through July 2020 with 73 heads of household, 37 caregivers of children < 5 years old, and 21 member… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 33 publications
6
29
0
Order By: Relevance
“…In terms of household behaviours, we saw majority of households reported cooking more, cleaning more and spending more time indoors during Lockdown Levels 5 and 4 compared to the month before. A study in rural Odisha, India, reported 41% of respondents having changed their household cleaning practices as a result of the COVID-19 outbreak or Lockdown [ 23 ]. Of these, 34% of respondents reported cleaning their house more frequently, and made mention of using water with phenyl, detergent, shampoo, or bleaching powder when washing floors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of household behaviours, we saw majority of households reported cooking more, cleaning more and spending more time indoors during Lockdown Levels 5 and 4 compared to the month before. A study in rural Odisha, India, reported 41% of respondents having changed their household cleaning practices as a result of the COVID-19 outbreak or Lockdown [ 23 ]. Of these, 34% of respondents reported cleaning their house more frequently, and made mention of using water with phenyl, detergent, shampoo, or bleaching powder when washing floors.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 34% of respondents reported cleaning their house more frequently, and made mention of using water with phenyl, detergent, shampoo, or bleaching powder when washing floors. Similarly, 13% of respondents either started using or make use of more disinfectant or detergent when cleaning their house [ 23 ]. These findings are in keeping with the “at home lockdown vicious cycle” proposed by Domínguez-Amarillo et al [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The particular emphasis on avoiding large crowds and social distancing from others, wearing a face mask around others, frequent hand washing with soap, and avoiding touching one's face (WHO, 2020). 3,4 Additionally, the SARS-CoV-2 virus has been detected in feces of infected individuals, leading to the possibility that fecal-oral transmission could also play a role in virus transmission, particularly in low-and middle-income countries (LMICs) with high rates of open defecation, ineffective fecal sludge management, and poor access to safe drinking water (Pandey, et al, 2021& Bauza et al, 2021). 5,6 In addition (Huraimel et al, 2020 & Aboubakr et al, 2021) 7,8 stated that diarrheal symptoms have been found in some individuals infected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Additionally, the SARS-CoV-2 virus has been detected in feces of infected individuals, leading to the possibility that fecal-oral transmission could also play a role in virus transmission, particularly in low-and middle-income countries (LMICs) with high rates of open defecation, ineffective fecal sludge management, and poor access to safe drinking water (Pandey, et al, 2021& Bauza et al, 2021). 5,6 In addition (Huraimel et al, 2020 & Aboubakr et al, 2021) 7,8 stated that diarrheal symptoms have been found in some individuals infected with COVID-19. SARS-CoV-2 may have higher stability and longer survival times in diarrheal stools, which could increase the risk of environmental transmission along potential fecal-oral routes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation